PENTINGNYA KREASI HAKIM DALAM MENGOPTIMALKAN UPAYA PERDAMAIAN BERDASARKAN PERMA NO. 1 TAHUN 2002 TENTANG ACARA GUGATAN PERWAKILAN KELOMPOK - Nhara Prana Pradnyana, I Dewa Made; Atmadja, I Dewa Gede (Kertha Semaya : Journal Ilmu Hukum; Vol. 01, No. 06, Juli 2013)
The procedures of Class action is set out in Supreme Court Regulation Number 1 of 2002. In encouraging the parties to resolve the case through reconciliation, the Supreme Court Regulation Number 1 of 2002 has some weaknesses. The creation by the judge is assessed as an important role in covering up the weaknesses and optimizing the reconciliation efforts of the parties in dispute.
Keywords: class action, reconciliation, the creation by the judge